Negative pressure pulmonary edema after general anesthesia using the i-gel - Deok-hee Lee; Nawon Lee (Saudi Journal of Anaesthesia, 2024)
Negative pressure pulmonary edema (NPPE) is a rare complication that occurs mainly after tracheal extubation. We report a case of postoperative NPPE associated with the use of the i-gel. A 28-year-old woman was scheduled for an emergency right axillary sentinel lymph node excision. During emergence, the patient experienced a sudden onset of airway obstruction, and spontaneous ventilation through the i-gel was impossible. Pink and frothy secretions were noted in the i-gel and the patient's oral cavity. Positive airway pressure with 100% oxygen was applied using a facemask, and the patient was subsequently treated with high-flow oxygen therapy. In this case, laryngospasm or displacement of the i-gel was believed to be the cause of airway obstruction. We recognized that NPPE is likely to occur regardless of the airway device, and the use of the i-gel cannot completely eliminate the possibility of NPPE occurrence.